Implementation Of Information System for Shift Scheduling and Payroll Management at Mang Jana Rice Store - Nugraha, Arif Bakti; Akbar, Imannudin (Jurnal Computech & Bisnis (e-journal), 2024)
Shift planning and payroll management in small and medium-sized enterprises (SMEs) often face inefficiencies and inaccuracies due to manual processes. This research focuses on the implementation of an information system to overcome this challenge at Mang Jana Rice Shop, Bandung. The system aims to automate shift planning and payroll calculation, ensuring accuracy and operational efficiency. Using the case study method, this research involves the phases of needs analysis, design, development, testing, and implementation of the system. The resulting system integrates shift planning with payroll management, reducing payroll errors and optimizing employee scheduling. The system has been tested and evaluated, showing significant improvements in efficiency and user satisfaction. This research contributes to the digital transformation of SMEs by providing practical solutions for managing employee tasks. Further developments, such as mobile integration and advanced attendance tracking, are recommended to improve usability and functionality.